A comprehensive review on the prospects of multi-functional carbon nano onions as an effective, high- performance energy storage material. (30th April 2021) - Dhand, Vivek; Yadav, Mithilesh; Kim, Sang Hoon; Rhee, Kyong Yop
Abstract: The present review offers readers with an update over current and novel developments of carbon nano onions (CNOs) in recent years. Here we concisely detailed out the synthesis routes, growth mechanism in different synthetic routes, purification methods, chemical, electronic, optical, electro-magnetic and tribological properties, applications in energy storage sectors especially in the field of ion batteries and supercapacitors, polymeric composites of carbon nano onion, publication, patent-research trends data (1980–2020) and a brief market analysis respectively. Graphical abstract: Image 1 Highlights: A comprehensive review on carbon onions has been carried out. Review covers a wide range of publication, citation and patent metrics from 1980 to 2020(Present). Patent data starts from 1992 to 2020(present) as accessed from Scopus search tool. Data from web of science displays publication and citation trends from 1980 to 2020 (present). Review covers, synthesis, growth mechanism, purification, energy storage and polymer composite applications.